Prevalence of Urinary Incontinence in Women aged 20â59 years in Community Dwellings - Wardani, Ratuafni Shafrina; Judistiani, Raden Tina Dewi; Siddiq, Amillia (Althea Medical Journal, 2017)
Background: Urinary incontinene (UI) is the symptomof involuntary leakage of urine. Three types of urinary incontinence are stress UI, urge UI, and mixed UI. This study was aimed to determine the prevalence of urinary UI in women and to identify the most common type of UI.Methods: A descriptive study was conducted to 191 women age 20â59 in two villages in West Java, Indonesia. Subjects were visited door-to-door and interviewed using a standardized questionnaire for data collection. The study was conducted in February 2014. The variables of this study were age, parity, and the prevalence of urinary incontinence. The collected data were presented using frequency tabulation and percentage.Results: From 191 respondents, thirty eight subjects had UI. The prevalence of urinary incontinence was 19.90% which consisted of prevalence of stress UI (7.33%), urgency UI (9.43%), and mixed UI (3.14%). The prevalence of UI in 20â29 year age group was 3.23%, 30â39 year age group was 9.72%, 40â49 year age group was 27.69%, and 50â59 year age group was 52.17%. Prevalence of UI in nulliparous women was 5%, primiparous was 10.25%, multiparous with 2 childbirths was 23.61%, and multiparous with 3 childbirths or more was 26.67%.Conclusions: Prevalence of UI in women in community dwelling is 19.90%, which is higher than previous study from Indonesia and other Asian countries. Urgency UI is the most common type of UI. Prevalence of UI increases with age and parity.Â DOI:Â 10.15850/amj.v4n2.1070